User-interactive registration of bone with A-mode ultrasound. - Heger, S. (IEEE Engineering in medicine and biology magazine)
In this study, we investigated a registration technique based on a mechanically tracked A-mode ultrasound pointer for transcutaneous A-mode ultrasound pointer for transcutaneous, noninvasive palpation of bone surface. The principle has been exemplified for distal femur registration in total hip replacement surgery and has been evaluated in laboratory trials on a bone/soft-tissue model. Three different registration modes were demonstrated. Regarding clinical requirements, we constricted the areas of palpation to points and surfaces accessible through a minimal surgical portal in order to avoid additional trauma to soft tissue. Registration based solely on proximal surface points seems to be insufficient for clinical application. To avoid the invasive direct palpation of the condyles and epicondyles, we used the A-mode ultrasound pointer for noninvasive transcutaneous registration (Mode III). The resulting entire mean rms error was 0.59 mm (0.28°), which is significantly better and more reliable than a registration exclusively in the proximal part of the femur. During the ultrasound registration process, the computer-based assistance tool gave visual feedback to the user to guide the alignment of the transducer's beam axis to be perpendicular to the local bone surface. After five iterations, the final angle error of this approximation was in the range of ±2 degree and generally influenced by the contribution of the discretization angle error ΦDIS. Based on the consideration of the thickness of the soft-tissue and the geometry of the ultrasound probe, it is suggested that this is a sufficient accuracy in order to ensure a reliable ultrasound-based digitization of the bone surface. The overall mean registration time using A-mode ultrasound, including palpation, and matching, seems to be tolerable. The algorithm and interface for user-interactive A-mode ultrasound-based registration seem to provide efficient support for robust and accurate registration.